Cultural perceptions of psychological disturbances : the folklore beliefs of South African Muslim and Hindu community members. - Ally, Yaseen (My University, 2009)
Culture shapes the expression and understanding of psychological disorders and plays a role in the emergence of culture-specific syndromes. In particular, certain cultures endorse beliefs in witchcraft, spells and spirits, which fall under the concept „folklore‟. Folklore beliefs like witchcraft and spirit possession and their assumed impact on the manifestation of psychological disturbances persist today. It thus becomes apparent that these cultural aspects will have an impact on how psychological disturbances are experienced and treated in different communities. Given this, the concept of psychological disturbance needs to be aligned with the culture of the afflicted individual if one is to holistically understand and treat him or her. In addition, considering that many cultures include a belief in the spiritual self, a need to understand its‟ alleged role in psychopathology exists (Ashy, 1999; Eldam, 2001; Smith, 2005). 6 Consequently, if one is to effectively understand diverse communities, an exploration of the impact that spiritual beliefs have on community members‟ perceptions of psychological disturbance is imperative. By focusing on the folklore beliefs of South African Muslim and Hindu community members, this study aims to promote a deeper understanding of the impact that these beliefs have on perceptions of psychological disturbances. Data was collected from four focus group discussions with two Muslim and two Hindu groups, comprising a total of 22 individuals. The interview schedule based on the salient themes from the literature guided the direction of the interview. This also allowed for clarification and exploration of new information. The data was analysed using thematic content analysis after the researcher had „cross-tabulated‟ participant responses. This enabled the researcher to sift through the data in a systematic manner, identifying themes that were indicative of the research questions. Responses to the questions fell into three broad categories: the participants‟ understanding of psychological disturbances, the participants‟ understanding of spiritual illnesses, and the impact of religious and/or cultural beliefs on the participants. Perceptions of psychological disturbances were found to reflect religious and cultural beliefs. A lay understanding of psychological disturbances was also reflected by the participants.
Keywords: Cultural perceptions; Psychological disturbances; Folklore; Muslim community; Hindu community